Risk factors for autonomic and somatic nerve dysfunction in different stages of glucose tolerance - Dimova, Rumyana; Tankova, Tsvetalina; Guergueltcheva, Velina; Tournev, Ivailo; Chakarova, Nevena; Grozeva, Greta; Dakovska, Lilia (Journal of diabetes and its complications, 2017)
The present study evaluates autonomic and somatic nerve function in different stages of glucose tolerance and its correlation with different cardio-metabolic parameters. Four hundred seventy-eight subjects, mean age 49.3±13.7years and mean BMI 31.0±6.2kg/m2, divided according to glucose tolerance: 130 with normal glucose tolerance (NGT), 227 with prediabetes (125 with impaired fasting glucose (IFG) and 102 with isolated impaired glucose tolerance (iIGT)), and 121 with newly-diagnosed T2D (NDT2D), were enrolled. Glucose tolerance was studied during OGTT. Antropometric indices, blood pressure, HbA1c, serum lipids, hsCRP and albumin-to-creatinine ratio were assessed. Body composition was estimated by a bioimpedance method (InBody 720, BioSpace). Tissue AGEs accumulation was assessed by skin autofluorescence (AGE-Reader-DiagnOpticsTM). Electroneurography was performed by electromyograph Dantec Keypoint. Cardiovascular autonomic neuropathy (CAN) was assessed by ANX-3.0 method applying standard clinical tests. CAN was found in 12.3% of NGT, 19.8% of prediabetes (13.2% of IFG and 20.6% of iIGT), and 32.2% of NDT2D. The prevalence of diabetic sensory polyneuropathy (DSPN) was 5.7% in prediabetes and 28.6% in NDT2D. The panel of age, QTc interval, waist circumference, diastolic blood pressure, and 120-min plasma glucose was related to sympathetic activity (F [5451]=78.50, p<0.001). The panel of age, waist circumference, and QTc interval was related to parasympathetic power (F [3453]=132.26, p<0.001). HbA1c and age were related to sural SNAP (F [2454]=15.12, p<0.001). HbA1c and AGEs were related to sural SNCV (F [2454]=12.18, p<0.001). Our results demonstrate a high prevalence of autonomic and sensory nerve dysfunction in early stages of glucose intolerance. Age, postprandial glycemia, central obesity, diastolic blood pressure and QTc interval outline as predictive markers of CAN; hyperglycemia, glycation and age of DSPN.